Pemberdayaan Masyarakat dalam Pengelolaan Sampah Berbasis Ekonomi Sirkular di Kecamatan Ujung Tanah Kota Makassar (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2025)
This community service program aims to empower the community of Ujung Tanah District, Makassar City in circular economy-based waste management. Ujung Tanah District as a coastal area with high population density faces complex waste problems, especially waste that ends up in the sea and disrupts the coastal ecosystem. The activities were conducted in four urban villages, namely Ujung Tanah, Tabaringan, Pattingalloang, and Pattingalloang Baru, involving 120 households as direct participants. The implementation methods included socialization and education, waste sorting and processing training, establishment of Waste Banks, mentoring for recycled product creation, and marketing system development. The results showed a significant improvement in community knowledge about waste management, with average scores increasing from 45.2 to 82.6. Four active Waste Bank units were established with a total of 320 household customers. The managed waste volume reached 2.4 tons per month with an economic value of IDR 8,500,000 per month. Recycled products include ecobrick crafts, bags from plastic packaging, and compost fertilizer. This program successfully changed the community paradigm from dumping waste into the sea to managing waste as a source of income.